The Effect of Junior Weight Vest and Junior Weight Vest Training with Additional Loads on Crawl Style Swimming Speed Club Denpasar City - Ida Bagus Gede, Jaya Mahotama; I Gusti , Lanang Agung Parwata; Made , Agus Wijaya; Wahjoedi, wahjoedi (Jurnal Pendidikan Kepelatihan Olahraga Undiksha, 2024)
This study aimed to determine the effect of Junior Weight Vest training, Junior Weight Vest training with additional weights, and Junior Weight Vest training with additional weights is more effective than Junior Weight Vest training in increasing crawl style swimming speed. The study used a pseudo-experimental research design with a Pretest-Posttest Control Group Design. 40 Denpasar City swimming athletes chose as the research subjects were divided into 3 groups; experimental group 1 with Junior Weight Vest training, experimental group 2 with Junior Weight Vest training with additional weights, and conventional training control group. The data obtained in the form of crawl swimming style speed which was then calculated the gain score value and tested the hypothesis. The results showed that Junior Weight Vest training and Junior Weight Vest training with additional weights increased crawl style swimming speed significantly, and Junior Weight Vest training with additional weights was more effective in increasing the crawl style swimming speed of Denpasar City athletes than Junior Weight Vest training.